As placas de pedra: estudo exegético de um objeto marcante nas tradições exodais - Weber, Fabíola (2020)
With forty-three presences in the Hebrew Bible, the so-called “stone plates” gain a unique representation in the Exodus narrative, which presents the founding event of the religion of Ancient Israel. It is worth discovering more precisely the symbolic connotations of such object. Thus, the research invests in a detailed and, therefore, exegetical study of the object at hand, investigating its materiality, its content, the matter of authorship and its permanence. It is reported that the plates were made of stone. For this reason, the concept of “plates” was chosen here instead of the word “boards”, because boards, in principle, lead us to think about the materiality of wood. Other details will be addressed: the circumstance that there were two; the idea that the inscription extended on both sides; the fact that there was a first pair of plates, which, after their destruction by Moses, was replaced by a second pair of plates; the fact that were carved by Moses, but received the writing from God. Along with this, places gain importance around this object: at times Mount Sinai, at others the ark. Finally, it is observed, par excellence, how Exodus traditions value what could be read on the plates, naming the content as instruction, commandments, ten words, testimony, and/or covenant words. Thus, they have probably become the most symbolic and representative object with regard to the exodus event and thus to the history of salvation experienced by Israel. Iconography reveals this to the present day, precisely by continuing to present Moses, over again, with the stone plates in his arms